PENGARUH ADITIF SERBUK BAN LUAR KENDARAAN RODA DUA BEKAS PAKAI PADA CAMPURAN HRS-WC - Pebrina Stiani (Universitas Lambung Mangkurat, 2023)
Waste tires from motorized two-wheeled vehicles is one of the used materials with a relatively high amount. Until now, used tires are only used as crafts. Burning used tires can also cause harmful pollution effects for the environment. By adding used tire powder as a mixture of asphalt, is one way to solve this problem. Has a goal to find the value of KAO value in the resulting mixture composition and specify additional effects used tire powder HRS-WC layer for marshal properties. The Marshall test has two steps, the first one calculates KAO value using a variety of asphalt content 6.5%, 7%, 7.5%, 8%, 8.5% and the KAO value of 7.78%. In the second stage, we use the configuration and KAO values obtained in the first stage of testing and modify them tire powder added 2%, 4%, 6%, 8%, 10% by weight of asphalt KAO. The results of the Marshall characteristic test without and with tire powder added have an increase in the Marshall stability value. From Marshall's tests and calculations, obtained 4%, 6%, 8% meet the specifications. The best percentage is 8% by weight of KAO asphalt which has a stability value of 1473.45 kg, voids in aggregate (VMA) 20.95%, voids in mixture (VIM) 3.33%, voids filled with bitmen (VFB) 85.37 %, Marshall quotient (MQ) 338,873 kg/mm.